Relationships and Connectedness: Weak Ties that Help Social Inclusion Through Public Access Computing - Gomez, Ricardo; Barón Porras, Luis Fernando (My University, 2013)
Of all the benefits public access to computers (PAC) offer users, the most valued by users are having more information for stronger relationships, better learning, and effective transactions. This article analyzes the most salient benefit, more information for stronger relationships with friends and family. Results of a qualitative study among users of libraries, telecenters, and cybercafés in Colombia, South America, show that social media and personal relationships can also have an important community and sociopolitical dimension. By fostering a sense of belonging and connectedness to community and to a larger world, PAC usage often leads to feelings of empowerment and development of social capital, two intangible factors that are critical for community development. This study used a mixed-methods approach, combining surveys and interviews in five regions of the country, to uncover the benefits of PAC for underserved communities. Its findings contribute new insight about the impact of information and communication technologies on community development and social inclusion. © 2013 Commonwealth Secretariat.
Keywords: Ciencias sociales; Social sciences; Acceso público a las computadoras; Public access to computers; Tecnología de la información y la comunicación (TIC); Information and communication technologies; Inclusión social; Social Inclusion